Late-Quaternary Environments of the United States : the Late Pleistocene. - Wright, H. E. (University of Minnesota Press, 1979)
To many, the Pleistocene Epoch, which constitutes the earlier and major part of the Quaternary Period, is synonymous with the glacial ages and is viewed as a time of dramatic environmental change. Although there now is abundant evidence that glaciations occurred not only during the Pleistocene but through much of the Tertiary Period as well, and therefore are more appropriately considered as late-Cenozoic phenomena.